Furry Vengeance - Fraser, Brendan; 1968-; Jeong, Ken; 1969-; Shields, Brooke; 1965- ([United States], 2010)
Sometimes four legs are better than two. Dan just moved his wife and son to the woods to take a new job with a supposedly eco-friendly housing development. But the fur, and Dans temper, is sure to fly when the local critters learn of the bleak plans for their forest home and stop at nothing to halt construction. Bonus material included.
Keywords: Ecological houses; Drama; Families; Drama; Housing developers; Drama; Sustainable architecture; Drama